THE EFFECT OF MUDHARABAH AND MUSYARAKAH FINANCING ON THE PROFITABILITY OF ISLAMIC GENERAL BANKS FOR THE 2020-2021 PERIOD - Ahmad Akram Tjoteng; Fathoni Zoebaedi; Mira Munira (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2022)
Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh pembiayaan mudharabah dan musyarakah terhadap profitabilitas Bank Umum Syariah (BUS) selama periode 2020-2021. Penelitian ini menggunakan teknik analisis data deksriptif dengan metode pendekatan kuantitatif. Selain itu, teknik pengumpulan data yang digunakan adalah metode kepustakaan dan dokumentasi. Adapun hasil penelitian menunjukkan bahwa adanya pengaruh pembiayaan mudharabah dan musyarakah yang signifikan terhadap profitabilitas Bank Umum Syariah (BUS) selama periode 2020-2021. Kata Kunci: Pembiayaan Mudharabah, Pembiayaan Musyarakah, Profitabilitas Ekuitas Abstract The development of Islamic economics in Indonesia, especially in the Islamic banking industry, has experienced very rapid growth. This is evidenced by the increasing number of Islamic banking institutions. This is because Islamic banking puts forward the values of Islamic teachings so that it adheres to a profit-sharing system. The implementation of the profit-sharing system generally includes financing with the contracts: mudharabah and musyarakah. As an Islamic financial institution that also carries out economic activities, making a profit is something that cannot be avoided, especially regarding the sustainability of the institution. Because with the profit earned, investors can do business with the bank, especially in terms of equity participation with the provision of profit-sharing. This research aims to determine whether there is a significant effect of profit–sharing financings on the profitability of Islamic General Banks in Indonesia by a certain period, using descriptive analysis with a quantitative approach. The final result of this research shows that there was a significant and negative effect between mudharabah financing and the profitability of equity, on the other hand, there was a significant and positive effect between musyarakah financing and the profitability of equity. Keywords: Mudharabah Financing, Musyarakah Financing, Profitability of Equity